2010
DOI: 10.1007/s11258-010-9738-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of tree species richness in Jalisco, Mexico: relation to topography, climate and forest structure

Abstract: Abstact The objective of this study was to identify the major environmental variables and components of forest structure associated with variability in tree species richness on a network of 806 permanent plots in the State of Jalisco, Mexico. Tree data recorded on the sample plots were used to characterize tree species richness by forest type and climatic conditions (temperature and precipitation) in the State. Species composition and other diversity indices were also calculated. Explanatory variables identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
2
6
0
6
Order By: Relevance
“…Si bien, las It is observed that the higher values in tree density and average diameter i n BC fragments are relevant and can affect the local variability of species richness. This agrees with some structural patterns detected by Reich et al (2010) which stat that the tree species richness of Jalisco state can be explained by the kind of forest cover, altitude, tree basal area, canopy cover and winter rainfal l.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Si bien, las It is observed that the higher values in tree density and average diameter i n BC fragments are relevant and can affect the local variability of species richness. This agrees with some structural patterns detected by Reich et al (2010) which stat that the tree species richness of Jalisco state can be explained by the kind of forest cover, altitude, tree basal area, canopy cover and winter rainfal l.…”
Section: Discussionsupporting
confidence: 91%
“…The time-space patterns of vegetation have been interpreted as a result of the influence of two kinds of gradients: a) the limiting environmental factors such as light, temperature, water, soil nutrient, for example; and b) the natural or human disturb (Jardel et al , 2004). For example, the topographic variation (altitudinal gradient) and the several types of soil are physical variables taken into account in the general hypothesis, that help to explain the species diversity at local geographic scales used in other mountain ecosystems in Mexico (Jardel et al , 2004;Cuevas et al , 2008;González-Espinosa et al, 2008;Reich et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, working with big data sets ecologists should be ready to work collectively in order to collect, preserve and share the data across projects and research groups (Hampton et al 2013). Good examples for such data can be found in Perry et al (2002), Watt et al (2009), Reich et al (2010 and Pongpattananurak et al (2012).…”
Section: Spatial Data Typesmentioning
confidence: 99%